A Shadowinside the Uterus after 6 Weeks of LSCS, Unexpected Presentation, A Source of Anxiety - Shama Chaudhry'; Rubina Hussain (ziauddin University, 2024)
ABSTRACT Intrauterine foreign body detection can be a diagnostic dilemma. Retention of a foreign body for long duration may lead to serious morbidity .We are reportinga case of A 20 year old GiP1+0 who wasreferred to tertiary care hospital with complaints of low grade fever, severe colicky whole abdominal pain, nausea, vomiting , watery loose motions for 1 day & with systemic manifestations of sepsis. She had lower segment caesarean section due to breach presentation in a private clinic 6 weeks back .After that she remained uneventful till this presentation. At presentation she had leukocytosis & raised CRP. CT scan whole abdomen showed hyper denseforeign bodyin the uterine cavity in the lower segment. She was started with antibiotics (imipenem & metronidazole) &EUA (Examination under Anaesthesia), Diagnostic D&C &removalof foreign body underguidance of mobile fluoroscopic system "portable C-arm" done. Foreign body came out to be solid misoprostol tablet. Key Words: EUA, Leukocytosis, CRP(C Reactive Protein), Mobile Fluoroscopic System "Portable C-Arm.